Analysis of The Implementation of The "My School, My Islamic Boarding School" Program on The Religious Character of Elementary School Students - Ari Dwi Atmojo; Subuh Anggoro; Ristiana Dyah Purwandari (Journal of Social Research, 2026)
This study investigates the implementation of the “Sekolahku Pesantrenku” program in shaping the religious character of elementary school students. The background of this research is the increasing concern over moral degradation among students in the 21st century, which requires schools to strengthen character education through structured religious habituation. The purpose of this study is to analyze the implementation process of the program, identify supporting and inhibiting factors, and examine its impact on students’ religious character development. This research uses a qualitative descriptive approach with a case study design conducted at SD Negeri 1 Karangmangu. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and parents. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and drawing conclusions. The results show that the program is implemented through daily, weekly, and integrated curriculum activities such as congregational prayers, *Qur’an* recitation, memorization of short *s?rahs*, and moral habituation. The findings indicate that the program significantly improves students’ discipline, worship habits, moral behavior, and social attitudes. Supporting factors include teacher role modeling, parental involvement, and school commitment, while challenges include differences in student abilities and limited time allocation. In conclusion, the *“Sekolahku Pesantrenku”* program effectively strengthens students’ religious character through continuous habituation and integrated learning practices, although improvements in monitoring and consistency are still needed to maximize its impact.